Effect of Zinc and Boron on the Yield and Quality Traits of the Broccoli under the Kanpur Agro Climactic Region (Brassica oleracea Var. italica L.) - , Saurabh Kumar, Vinay Joseph Silas, Jitendra Kumar, Kartikay Bisen, Ashish Kumar (Archives of Current Research International, 2025)
A field experiment was conducted during rabi 2024 at Horticulture Research Farm, The Faculty of Agricultural Sciences and Allied Industries, Rama University, Kanpur (U.P.), conducted an experiment laid out in a Randomized Block Design (RBD) with eight treatments, each replicated three times, based on one year of experimentation. The treatments were as follows: T0: Control, T1: RDF + Zinc foliar application @ 0.5%, T2: RDF + Zinc soil application @ 25 kg/ha, T3: RDF + Zinc soil application @ 25 kg/ha + Zinc foliar application @ 0.5%, T4: RDF + Boron foliar application @ 0.5%, T5: RDF + Boron soil application @ 2 kg/ha, T6: RDF + Boron soil application @ 2 kg/ha + Boron foliar application @ 0.5%, T7: RDF + Combined foliar application of Boron @ 0.5% and Zinc @ 0.5%. The unit plot size was 4.5 m². The plant spacing was maintained at 60 cm between rows and 45 cm between plants, with a total of 10 plants in each plot. The treatments were randomly allocated to unit plots in each replication. The results revealed that the application of T7 (RDF + combined foliar application of Boron @ 0.5% and Zinc @ 0.5%) recorded the highest plant growth, yield, and quality of broccoli compared to other treatments. It also achieved the highest gross return, net return (Rs. ha⁻¹), and benefit-cost ratio.